THE PROTECTION OF CHILDREN’S RIGHTS IN INDONESIA UNDER LAW NO. 35 OF 2014 ON CHILD PROTECTION AND CONVENTION ON THE RIGHTS OF THE CHILD: CASE OF ANGELINE - Teguh Abdullah Aldiansyah (FH IH 16 UMY 055, 2016)

(untitled)
Nowadays, the issue of children’s rights has brought to the attention of the international community, including Indonesia. The most tragic case happened in Indonesia is the murder of Angeline, an eight-year-old girl, found buried behind her foster mother’s home in Bali. Angeline case is a reminder for the government to ensure the implementation of Law No. 35 of 2014 on Child Protection, which has not been exercised properly. This research uses normative legal research with statute and case approaches. By using a qualitative descriptive method, this study analyzes the implementation of the current protection of rights of children in Indonesia based on the perspective of Convention on the Right of the Child (CRC) and Law No. 35 of 2014.The results show the protection of children’s right in Indonesia is not fully implemented yet, although Indonesia has already ratified the Convention on the Right of the Child, aside of the enactment of Children’s Rights Act. It is identified that in the case of Angeline, both Convention and Indonesian Law are not applied properly, especially the ratification of CRC because it is only based on Presidential Decree. Thus, the government has to disseminate all the regulations related to how the society becomes part of the parties who are able to protect the children surrounding them. Furthermore, Indonesia also has to increase the status of Presidential Decree into an Act, since there is no sanction can be imposed to the guilty within the Presidential Decree.